1998
DOI: 10.1007/s003359900869
|View full text |Cite
|
Sign up to set email alerts
|

A major quantitative trait locus co-localizing with cholecystokinin type A receptor gene influences poor pancreatic proliferation in a spontaneously diabetogenic rat

Abstract: The Otsuka Long-Evans Tokushima Fatty (OLETF) rat is an animal model for obese-type, non-insulin-dependent diabetes mellitus (NIDDM) in humans. The OLETF rat has poor capacity for pancreatic proliferation, which may be the critical pathogenetic event in NIDDM development. Our investigation was designed to identify quantitative trait loci (QTLs) responsible for poor pancreatic proliferation by examining compensatory proliferation of the pancreatic remnant after partial pancreatectomy and performing a genome-wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The essential contribution of CCK1R for pancreatic regeneration following pancreatectomy or pancreatic duct ligation has been demonstrated in OLETF rats as well as in a congenic rat carrying a CCK1R null allele (321,322,332,333). The importance of CCK for normal pancreatic growth has also been reported in this rat strain or in control rats after FIG. 6.…”
Section: Exocrine Pancreasmentioning
confidence: 79%
“…The essential contribution of CCK1R for pancreatic regeneration following pancreatectomy or pancreatic duct ligation has been demonstrated in OLETF rats as well as in a congenic rat carrying a CCK1R null allele (321,322,332,333). The importance of CCK for normal pancreatic growth has also been reported in this rat strain or in control rats after FIG. 6.…”
Section: Exocrine Pancreasmentioning
confidence: 79%
“…Since genetic and environmental factors can be strictly controlled when inbred animal models are used, such models are invaluable for the dissection of complex diseases. Loci contributing to type 2 diabetes and related traits in diabetic animal models have been reported using quantitative trait locus (QTL) mapping analyses (GK rat [2,3], OLETF rat [2,[4][5][6][7], SDT rat [8], NSY mouse [9], NZO mouse [10,11], TSOD mouse [12], KK mouse [13], KK-Ay mouse [14,15] and TH mouse [16]). …”
Section: Introductionmentioning
confidence: 99%
“…Many recessive genes on several chromosomes including the X chromosome are involved in the induction of diabetes in OLETF rats. It is also observed that the OLETF rats carry a null allele for the cholecystokinin A receptor which may be related to the regulation of food intake [50, 51]. The pancreatic islets of OLETF rats change progressively, and less than 9 weeks of age, the islets just exhibit mild lymphocyte infiltration, then show hyperplastic alterations and fibrosis in or around islets at around 10 to 40 weeks of age, finally more than 40 weeks, represent atrophy of islets [52].…”
Section: Spontaneous Type 2 Diabetic Rodent Modelsmentioning
confidence: 99%